2010
DOI: 10.1002/uog.7521
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of fetal head descent using the ‘angle of progression’ on transperineal ultrasound imaging is reliable regardless of fetal head station or ultrasound expertise

Abstract: Objectives (overall ICC, 0.72; 95% CI,. ICCs were 0.82 (95% CI, 0.81 (95% CI, (ICC, 0.86; 95% CI,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(119 citation statements)
references
References 21 publications
4
108
0
7
Order By: Relevance
“…The angle between these two lines (AOP) was measured. This measurement is independent of the obstetrician's experience, based on the identification of two visible bone structures easily [9,10]. All ultrasound examinations were carried out by the authors using an Acuson Antares machine with a 2-3MHz convex transducer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The angle between these two lines (AOP) was measured. This measurement is independent of the obstetrician's experience, based on the identification of two visible bone structures easily [9,10]. All ultrasound examinations were carried out by the authors using an Acuson Antares machine with a 2-3MHz convex transducer.…”
Section: Methodsmentioning
confidence: 99%
“…Molina et al [7], among other authors [13,14], evaluated the reproducibility of the different ultrasound parameters used to assess the evolution of delivery and concluded that the angle of descent is the most reproducible parameter for measuring fetal head progression during labor, whereas Duckelmann et al [10], showed that the determination of this ultrasound parameter is also independent of the professional's experience.…”
Section: Spontaneous Vaginal Delivery Occurred In 72 (71%) Women Insmentioning
confidence: 99%
“…Digital transvaginal examination, which is highly dependent on the clinician's ability and is still regarded 'gold standard' for obstetric practice, has several limitations. 3 A relatively new potential purpose for ultrasound in tracking the progress of labor is therefore developing and the process of gathering knowledge is underway to demonstrate its effectiveness and applicability. 4 By merit of its safety and non-invasive nature, given appropriate circumstances intrapartum ultrasound examination is applicable for most, if not all, indications currently considered in the antepartum arena.…”
Section: Intrapartum Ultrasonography For Prediction Of Vaginal Delivementioning
confidence: 99%
“…Recent surveys have indicated that ultrasound imaging might allow dynamic and objective quantification of the degree of fetal head descent in the birth canal. 3 Various sonographic modalities have been employed in the intrapartum determination of the fetal head engagement. 5 Success in nonoperative vaginal birth mainly depends on the fetal descent and thus it is a central element in the clinical evaluation of progress of labor.…”
Section: Intrapartum Ultrasonography For Prediction Of Vaginal Delivementioning
confidence: 99%
See 1 more Smart Citation